Periode Konsepsi Awal Kejadian Manusia (Pertemuan Sperma dan Ovum) dan Nilai-Nilai Pendidikan Yang Terkandung di Dalamnya - Abas, Erjati (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2015)
Children's education in Islam is not just beginning when the child was born, even in the early days will be the establishment of the child, Islam has taught to educate children. The preparation needs to be done is to start and conduct biological relationships legally and properly, and pray to Allah that his actions are not the demon and futile. In addition, the petition relies solely on Allah blessed with a child so pious. The values of the child's education conception period can also be implemented in Islamic religious education began in the formulation of objectives, materials, methods, evaluation, and the role of educators, so that the objectives of Islamic education for the birth of human morality are achieved with optimal.